Seroprevalence of porcine cysticercosis in Maharashtra - WAVHAL, NILAM; PATURKAR, ASHISH; VAIDYA, VILAS; WAGHMARE, RUPESH; ZENDE, RAVINDRA; MOON, SHILPA (The Indian Journal of Animal Sciences, 2019)
Porcine cysticercosis is caused by Cysticercus cellulosae, a larval stage of parasite Taenia solium. Humans get infected by consuming eggs of T. solium through contamination of food and water. Owing to economic and zoonotic importance of porcine cysticercosis in India, a research plan was designed to study seroprevalence of cysticercosis in Maharashtra. Blood samples (172) were collected from different regions. The seroprevalence of cysticercosis by ELISA, FTA and western blot was 8.5%, 7.5% and 6.98%, respectively. Cohen’s kappa coefficient was used to analyse for the percentage of agreement with meat inspection test. The sensitivity and specificity between ELISA and FTA (k=0.958) showed no significant difference. The study indicates that ELISA and FTA were more sensitive than western blot. Western blot of whole cyst antigen revealed immunoreactivity at 42 to 250 kDa bands. The seroprevalence of porcine cysticercosis in Maharashtra had increased significantly. FTA is easier to perform and faster than ELISA test. This simple test appears to be suitable for practical use at field level, especially for largescale ante-mortem screening of pigs against cysticercosis.